Study of the oral hypoglycemic activity of Moringaoleifera leaves alone and in combination with Glibenclamide in streptozotocin induced diabetic albino rats - Naidu, Sushma V.; R. N., Suresha; M. K., Jayanthi; A. M., Satish; H. L., Kalabharathi; V. H., Pushpa (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Oringaoleifera is a widely used plant with high medicinal value, well known for its pharmacological actions and is used in various conditions. It has been reported to have many biological properties like anti-inflammatory, antimicrobial, antispasmodic, antitumour including antidiabetic activity. Methods: The study was carried out in Wistar albino rats with body weight 150-250gms. Diabetes was induced by injecting Streptozotocin intraperitoneally- dose 55 mg/kg BW. Animals were divided into 5 groups with 6 animals in each group. First group (Control) was given 2% gum acacia. Other 4 groups were induced diabetes by giving Streptozotocin. Diabetic control group received gum acacia (0.5 ml), Standard group received Glibenclamide (0.5mg/kg BW), Test group received Moringaoleifera extract (300mg/kg) and Test+ Standard group receiving combination of Moringaoleifera and glibenclamide at half the above doses. All drugs were given orally for 28 days and blood glucose levels analyzed using Glucometer on Day 0 before drug and on D1, D3, D7, D14, D21, and D28. Data were statistically analyzed by ANOVA and Tukey‘s Post Hoc test. Results: Hypoglycemia produced by Moringaoleifera extract was significant (p<0.001) when compared to diabetic control group from day 7 to day 28. The percent reduction of blood glucose level was 52.9% as compared to Glibenclamide group 61.3%. The combination group also showed significant hypoglycemic activity the percentage reduction being 56.44%. Conclusions: Thus, Moringaoleifera decreased blood glucose level efficaciously as compared to diabetic control group and similar to standard group at p<0.001.